1980
DOI: 10.1017/s0033291700047401
|View full text |Cite
|
Sign up to set email alerts
|

Sub-syndromes of tardive dyskinesia

Abstract: SYNOPSISA reliable method for recording the site and duration of purposeless movements was devised. With this method 267 subjects were studied, 182 of whom had been exposed to neuroleptics. The results were submitted to a principal components analysis and 3 movement dimensions emerged. One group of movements resembled a parkinsonian syndrome. The other 2 groups of movements both conformed to the generally accepted criteria for tardive dyskinesia. These groups were: (1) head and neck movements and (2) trunk and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
32
0

Year Published

1981
1981
1998
1998

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 14 publications
5
32
0
Order By: Relevance
“…Alternatively, orofacial and limb/truncal TD have been proposed as separate and perhaps pathophysiologically distinct clinical subsyndromes (Barnes and Kidger, 1979;Glazer et al, 1988;Gureje, 1989). Evidence favoring topographical subsyndromes has been derived in part from the results of multivariate statistical analysis (Kidger et al, 1980) and from observations of dierential responses to pharmacological interventions (Greil et al, 1985). In addition, and in agreement with the results of the present study, Barnes et al (1983) found that the severity of orofacial but not limb/truncal TD was positively associated with age.…”
Section: Discussionsupporting
confidence: 84%
“…Alternatively, orofacial and limb/truncal TD have been proposed as separate and perhaps pathophysiologically distinct clinical subsyndromes (Barnes and Kidger, 1979;Glazer et al, 1988;Gureje, 1989). Evidence favoring topographical subsyndromes has been derived in part from the results of multivariate statistical analysis (Kidger et al, 1980) and from observations of dierential responses to pharmacological interventions (Greil et al, 1985). In addition, and in agreement with the results of the present study, Barnes et al (1983) found that the severity of orofacial but not limb/truncal TD was positively associated with age.…”
Section: Discussionsupporting
confidence: 84%
“…These cases are generally considered to be phenomenologically indistinguishable from tardive dyskinesia,I82021 and a similar pathophysiological basis has been suggested. 22 In this study we set out to investigate the nature and distribution of semi-purposeful and purposeless spontaneous movements in psychiatric patients treated with antipsychotic drugs, compared with those observed in a control population. 540 Method The first group of subjects consisted of 182 psychiatric patients, all of whom had been receiving antipsychotic medication for at least one year.…”
mentioning
confidence: 99%
“…For each set of three ratings a single "modal" score was derived according to a method previously described. 22 These modal scores, reflecting "duration" of movement, are used exclusively in the Results section.…”
mentioning
confidence: 99%
“…First, multifactorial analysis (Glazer et al 1988;Kidger et al 1980) suggests that an orofacial movement factor was separate from a limbtrunk movement factor. Secondly, differential response to drug treatment has been reported to the 2 types (Bobruff et al 1981;Gardos et al 1976).…”
Section: Tardive Dyskinesiamentioning
confidence: 99%